USING ONLINE TOOLS IN ENGLISH AS A FOREIGN LANGUAGE CLASSES - Bobomuratova Nargiza Hayrullayevna (PEDAGOGS, 2023)
Annotation. This article explores the integration of online tools, specifically the Jeopardy game, in English as a Foreign Language (EFL) classes to enhance language learning. The study investigates the impact of gamification on student engagement and language acquisition. Utilizing a mixed-methods approach, the research analyzes both qualitative and quantitative data to draw meaningful conclusions about the effectiveness of incorporating online games in EFL instruction.